Need Analysis for Improving Mathematics Education with STEAM: Exploring Batik Pattern Design - Nursanti, Yuli Bangun; Wulandari, Arum Nur (Universitas Sebelas Maret, 2023)
Mathematics has historically been perceived as challenging for many students. However, mathematics has significant potential for developing creativity, especially in solving problems in complex scenarios. The STEAM approach (Science, Technology, Engineering, Arts, and Mathematics) systematically integrates mathematics with various disciplines to foster intellectual growth, critical thinking, and creative thinking by highlighting the interrelationships between these fields. STEAM positions mathematics as a field that can build on other areas, including the arts. This idea is clearly illustrated through its integration with culture, especially the art of batik, where mathematical elements such as geometric patterns, symmetry principles, rotation, and reflection are depicted in the process. This study aims to increase students' understanding of the art of batik and the application of mathematics to arouse students' interest in mathematics. The study involved 41 elementary school students covering grades 4, 5, and 6. They initially completed a pre-test questionnaire comprising 25 questions that investigated their basic knowledge of batik and their level of interest in mathematics. Educational activities with the theme of mathematics, including geometry, batik, and the use of Microsoft Word, to explore creative digital batik pattern designs are given as initial treatment. After this treatment, participants were given a post-test. This study showed a marked increase in students' understanding of batik and their knowledge of geometric mathematics, especially in designing batik patterns.